2013
DOI: 10.3748/wjg.v19.i1.108
|View full text |Cite
|
Sign up to set email alerts
|

Double guidewire techniquevstranspancreatic precut sphincterotomy in difficult biliary cannulation

Abstract: When free bile duct cannulation was difficult and selective pancreatic duct cannulation was achieved, DGT and TPS facilitated biliary cannulation and showed similar success rates. However, post-procedure pancreatitis was significantly higher in the DGT group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 18 publications
2
68
1
2
Order By: Relevance
“…Biliary cannulation rates and the time to cannulate were similar, but the overall incidence of PEP was significantly lower in the TPS group (11% vs 38%, P<.01). 61 TPS is a viable option, although not commonly used in North America. The success of this approach critically depends on the appropriate cutting current to minimize any coagulation effect and to avoid a deeper cut to prevent pancreatic parenchymal insult.…”
Section: Transpancreatic Septotomymentioning
confidence: 99%
“…Biliary cannulation rates and the time to cannulate were similar, but the overall incidence of PEP was significantly lower in the TPS group (11% vs 38%, P<.01). 61 TPS is a viable option, although not commonly used in North America. The success of this approach critically depends on the appropriate cutting current to minimize any coagulation effect and to avoid a deeper cut to prevent pancreatic parenchymal insult.…”
Section: Transpancreatic Septotomymentioning
confidence: 99%
“…Saját gyakorlatunkban ötvöztük a két módszert, a betegek mintegy 70%-át papillotommal sikeresen és alacsony PEP-arány-nyal kanüláltuk, és öt sikertelen kísérlet után alkalmaztunk vezetődrótot [8,18]. A kettős vezetődróttal való kanülálás [29] helyett az előmetszés előnyösebbnek tű-nik [6,30].…”
Section: Vezetődróttal Végzett Intubálásunclassified
“…DGW technique was not superior when compared to pre-cut or cannulation techniques with a conventional guidewire, and the risk of acute pancreatitis was increased. [12][13][14] Few studies evaluated DGW in a standardized strategy of CBD cannulation. However, two recent studies showed that DGW was effective in addition to conventional cannulation techniques when included in a standardized protocol.…”
Section: Introductionmentioning
confidence: 99%